2017
DOI: 10.1093/asj/sjw241
|View full text |Cite
|
Sign up to set email alerts
|

Drainless Abdominoplasty Using Barbed Progressive Tension Sutures

Abstract: We describe our current technique of drainless abdominoplasty using barbed progressive tension sutures. The perioperative management and detailed steps of procedure are outlined, including indications for concomitantly performing liposuction and repair of diastasis of the rectus abdominis muscles. This approach reliably improves abdominal contour, minimizes complications, and is straightforward to learn and perform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Subsequently, the umbilical region is located where 4 points are made at 12, 3, 6 and 9 o'clock to finally perform an additional progressive tension suture 2 centimeters away from the midline with greater spacing and in a more random manner to achieve tissue adaptation to the degree of undermining obtained. Once the lower edge of the wound is reached, excess skin is removed, closing the dermis and skin in the usual way [8][9][10][11][12][13]. According to Pollock [1], the modification of the surgical technique, specifically the use of PTS in the abdominal flap, has shown a low incidence of complications since, in their study carried out in 2012 with 597 cases, reported a seroma occurrence rate of 0.1% with overall local complications of 4.2%, which represented a significant decrease from the figures obtained after switching from abdominoplasty with drains to the PTS technique.…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the umbilical region is located where 4 points are made at 12, 3, 6 and 9 o'clock to finally perform an additional progressive tension suture 2 centimeters away from the midline with greater spacing and in a more random manner to achieve tissue adaptation to the degree of undermining obtained. Once the lower edge of the wound is reached, excess skin is removed, closing the dermis and skin in the usual way [8][9][10][11][12][13]. According to Pollock [1], the modification of the surgical technique, specifically the use of PTS in the abdominal flap, has shown a low incidence of complications since, in their study carried out in 2012 with 597 cases, reported a seroma occurrence rate of 0.1% with overall local complications of 4.2%, which represented a significant decrease from the figures obtained after switching from abdominoplasty with drains to the PTS technique.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Maclas et. al [2] state that they agree with this, however they comment that one of the important limitations for the reproduction of the process is the time necessary to complete the technique, since approximately 20 to 50 minutes are required to perform 30 o 40 sutures that allow the abdominoplasty flap to be effectively attached to the abdominal wall, a situation that has sought to be corrected through the implementation of techniques such as the "padded" and "barbado" suture, among others [12,14,15]. On the other hand, Bromley [5] highlights the importance of remembering that regardless of the suture technique (continuous or interrupted), PTS placement is a technique that can be easily adapted to the different influencing factors.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…1,2,11,13 In 15 publications, suitable photographs were available (Table 4). 3,15,19,22,[24][25][26][27][28]33,36,40,48,49,60 The scar level ranged from 8.6 to 14.1 cm.…”
Section: Measurementsmentioning
confidence: 99%
“…65 A major focus has been on the elimination of drains. 13,14,29,36,37 The author uses a single suction drain, which is removed 3 or 4 days after surgery regardless of drainage volume. In some cases, when there has been very little bleeding at surgery and minimal fluid accumulation in the suction bulb, the drain is removed earlier.…”
Section: Seromasmentioning
confidence: 99%
See 1 more Smart Citation